OP0217 Ultrasound-Detected Synovitis and Tenosynovitis Independently Associate with Flare in Patients with Rheumatoid Arthritis in Clinical Remission. (9th June 2015) - Bellis, E.; Scirè, C.A.; Carrara, G.; Adinolfi, A.; Batticciotto, A.; Bortoluzzi, A.; Cagnotto, G.; Caprioli, M.; Canzoni, M.; Cavatorta, F.P.; De Lucia, O.; Di Sabatino, V.; et al.
Abstract : Background: Remission is the target of treatment in rheumatoid arthritis (RA). In clinically-defined remission, subclinical disease activity may persist leading to flare and joint damage progression. Musculoskeletal ultrasonography (MSUS) is a good candidate to overcome the limitations of clinimetric indexes. The role of MSUS synovitis is well-known in the literature but no data are available for tenosynovitis. Objectives: The study aims to evaluate the association between US synovitis (S) and tenosynovitis (T) and 6-month flare in RA patients in clinical remission. Methods: The STARTER study is a multicentre cohort study promoted by the Italian Society for Rheumatology. Ultrasonographers were selected by an inter-reader reliability exercise. Consecutive patients with RA and clinical remission underwent a full clinical evaluation and Grey Scale (GS) and power Doppler (PD) US exam (assessing -S and -T) at wrists, MCP, PIP and extensor/flexor tendon sheets. Six-month flare was defined as: 1) increase of >1.2 or >0.6 if final DAS28>3.2; 2) change in treatment; 3) change of >4 points in the flare questionnaire (FQ) if FQ<4 at baseline. The relationships between presence of GS-T/-S, PD-T/-S were evaluated by logistic models, presented as odds ratios (OR) and 95%CI, adjusted for pre-specified confounders. Results: A total of 427 patients were included in the analyses: 113 (26.5%) men, mean (SD) age 56.6 (13.4), median (IQR) disease duration 7.3 (3.8-13.5) years, median (IQR) remission duration 12 (8-24) months, RF positive 287 (67.4%), mean (SD) DAS28 2.2 (0.8), median (IQR) HAQ 0.125 (0-0.375), on DMARDs 322 (75.4%), on biologics 183 (42.9%), on glucocorticoids 187 (43.8%). GS-T was present in 198/373 (53.1%) patients, PD-T in 88/372 (23.7%) while GS-S in 270/368 (73.4%) and PD-S in 171/372 (46.5%). The association between US variables and flare is reported in the Table . Conclusions: MSUS PD-S confirms its predictivity on flare defined according to DAS28 definitions while PD-T is more specifically associated with patient-related flare and symptoms exacerbation. US-T should be take into account in the management of RA patients in clinical remission. Disclosure of Interest: None declared